Exergames in the rehabilitation of the mastectomized person: a Scoping Review - Baldaia, Cláudia Patrícia da Silva (2023)
Introduction: Exergames have been successfully utilized in healthcare, namelyin rehabilitation care. The present paper, authored by individuals who are aware of the potential of this technological resource, is intended to contribute to the construction of a rehabilitation nursing program that incorporates exergames for patients that have undergone breast cancer surgery. Methodology: We conducted a Scoping review study. The research was performed in the following databases; MEDLINE® (Medical Literature Analysis and Retrieval System Online), CINAHL® (Cumulative Index to Nursing and Allied Health Literature), SPORTDiscus, SCOPUS,SciELO (Scientific Electronic Library Online), Psychology and Behavioral Sciences Collection, Cochrane Central Register of Controlled Trials e PEDRo (PhysiotherapyEvidence Database) identifying all studies published by January 31, 2022, accordingwith Joanna Briggs Institute´s and PRISMA-ScR´s guidelines. Results: Thirteenarticles, published between 2015 and 2021, were selected. In total, there were 441participants. Platforms, such as Xbox and Nintendo Wii, that are compatible withgames that involve motion, were the most used. The duration of the interventionstrategies ranged from 15 days to 12 weeks. The majority of the interventions occurred in the late postoperative recovery phase. Intervention with exergames generated superior or similar results to traditional rehabilitation in terms of pain, upper limb functionality, range of motion, fatigue and quality of life. Conclusion: The present Scoping review emphasises the positive impact of the use of exergames in the rehabilitation of individuals with breast cancer. However, it is pertinent to conduct a greater number of scientific studies in this area that allow determining the type of game, time and frequency of intervention that optimize the level of effectiveness.   keywords: Breast Neoplasms; Exergames, Rehabilitation